A novel MAP3K7 mutation in a child with cardiospondylocarpofacial syndrome and orofacial clefting. Issue 2 (1st November 2022) - Shepherd, William Billal; Colaiacovo, Samantha; Campbell, Craig; Saleh, Maha
Abstract : Here we present the case of a patient with a novel de novo, likely pathogenic, heterozygous MAP3K7 variant (c.528dupT, p.G177WfsX5) causing cardiospondylocarpofacial syndrome (CSCFS). The variant, which falls in exon 6, is the first frameshift or non‐sense mutation to be connected to CSCFS and presents with a phenotype that shares features with other MAP3K7 ‐linked pathologies, including frontometaphyseal dysplasia 2 (FMD2) and the syndrome arising from an interstitial 6q15 deletions which envelop the gene. Other known mutations associated with CSCFS are plotted in black text (1, 2, 3).